Robust time series models with trend and seasonal components - Michele Caivano; Andrew Harvey; Alessandra Luati (SERIEs - Journal of the Spanish Economic Association, 2016)
We describe observation driven time series models for Student-t and EGB2 conditional distributions in which the signal is a linear function of past values of the score of the conditional distribution. These specifications produce models that are easy to implement and deal with outliers by what amounts to a soft form of trimming in the case of t and a soft form of Winsorizing in the case of EGB2. We show how a model with trend and seasonal components can be used as the basis for a seasonal adjustment procedure. The methods are illustrated with US and Spanish data.
Keywords: C22; G17; 330; Fat tails; EGB2; Score; Robustness; Student's t; Trimming; Winsorizing